The effect of increased water vapor from the Hunga Tonga-Hunga Ha'apai eruption on the Antarctic ozone hole - Wohltmann, Ingo; Santee, Michelle L.; Manney, Gloria L; Millan, Luis (Authorea, Inc., 2023)
The eruption of the Hunga Tonga-Hunga Ha’apai volcano on 15 January 2022 was one of the most explosive eruptions of the last decades. The unprecedented amount of water vapor injected into the stratosphere increased the stratospheric water vapor burden by about 10%. Using model runs from the ATLAS chemistry and transport model and Microwave Limb Sounder (MLS) satellite observations, we show that while 20-40% more water vapor than usual was entrained into the Antarctic polar vortex as it formed (e.g., typical values of 4.6 ppm at 21.5 km increased to 6.7 ppm), the direct effect of the increased water vapor on Antarctic ozone depletion was minor. This is caused by the very low temperatures in the vortex, which limit water vapor to the saturation pressure and tend to reset any anomalies in water vapor by dehydration before they can have an effect on ozone loss.